MENGHADAPI TANTANGAN RADIKALISME PENAFSIRAN AL QUR’AN DALAM PERSPEKTIF: PENDEKATAN MULTIKULTURAL DAN DIALOGIS - Moh. Akib (STAI Asy-Syukriyyah, 2024)
This article discusses the challenges of radicalism in the interpretation of the Koran and presents a multicultural and dialogical approach as an effective solution. Radicalism in religious interpretation often results in social tension and conflict between groups. In the Islamic context, the Koran is often misused to justify radical actions that are contrary to human values and tolerance. The multicultural approach emphasizes the importance of respecting diversity in understanding religion and culture, while the dialogic approach encourages dialogue between various groups to achieve a deeper and more inclusive understanding. This article analyzes how applying this approach can help overcome radicalism and promote social harmony and a more accurate understanding of the teachings of the Qur'an. Through this discussion, it is hoped that a broader understanding will emerge about the importance of a multicultural and dialogical approach in responding to the challenges of radicalism in the interpretation of the Al-Qur'an.